2011
DOI: 10.1167/iovs.10-7069
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Photosensitive (Melanopsin) Retinal Ganglion Cell Function in Glaucoma

Abstract: Persons with moderate and severe glaucoma have a dysfunctional ipRGC-mediated PIPR. Intrinsically photosensitive retinal ganglion cell function measured directly with the PIPR may become a clinical indicator of progressive changes in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
206
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(237 citation statements)
references
References 30 publications
8
206
1
17
Order By: Relevance
“…106,108 Dysfunction of ipRGCs in animal models of glaucoma have been corroborated by human studies because glaucoma patients with sleep disorders showed a reduction in the pupillary light response and suppression of nocturnal melatonin by light. [113][114][115][116][117][118] The potential role of ipRGCs has been described in other pathological processes. Concurrent regression of embryonic hyaloid vasculature and formation of the retinal vasculature occur postnatally in the mouse, 119 and the light response pathway that regulates both processes involves melanopsin.…”
mentioning
confidence: 99%
“…106,108 Dysfunction of ipRGCs in animal models of glaucoma have been corroborated by human studies because glaucoma patients with sleep disorders showed a reduction in the pupillary light response and suppression of nocturnal melatonin by light. [113][114][115][116][117][118] The potential role of ipRGCs has been described in other pathological processes. Concurrent regression of embryonic hyaloid vasculature and formation of the retinal vasculature occur postnatally in the mouse, 119 and the light response pathway that regulates both processes involves melanopsin.…”
mentioning
confidence: 99%
“…In a model of inherited glaucoma (mouse strain DBA/2J) in which IOP is elevated, melanopsin-expressing RGCs are not selectively spared (Jakobs et al 2005). Patients with early-stage glaucoma show no deficits in ipRGC function determined by the postillumination pupil response whereas in people with advanced glaucoma, ipRGC function was reduced (Feigl et al 2011). Conversely, axotomized melanopsin-expressing RGCs show enhanced survival compared to conventional RGCs in the mouse (Robinson and Madison 2004).…”
mentioning
confidence: 99%
“…A second study showed progressive loss in density, cell integrity and dendritic arborisation of ipRGCs in advanced stages of RP (Esquiva et al 2013) consistent with initial findings of ipRGC dysfunction in advanced AMD ). An example of this resistance to damage is shown in a study in patients with glaucoma that demonstrated the PIPR in patients with early glaucoma was similar to controls (Feigl et al 2011b), but lower in patients with advanced glaucoma (Feigl et al 2011b;Kankipati et al 2011). In patients with Leber's hereditary optic neuropathy (LHON), the sustained pupil response to blue light in the affected eye was similar to that in the healthy eye, suggesting a resistance to the intracellular metabolic disorder affecting the optic nerve caused by a genetic defect (Kawasaki et al 2010;Moura et al 2013).…”
Section: 6mentioning
confidence: 94%
“…IpRGCs have demonstrated enhanced survival after optic nerve injury and transection in rats (Li et al 2008;Perez de Sevilla Muller, Sargoy, Rodriguez & Brecha 2014) suggesting high injury resistance (Cui, Ren, Sollars, Pickard & So 2015), although studies in humans show ipRGC dysfunction in patients with glaucoma (Feigl, Mattes, Thomas & Zele 2011b;Gracitelli et al 2014;Kankipati, Girkin & Gamlin 2011) and more recently in glaucoma suspects (Adhikari et al 2016b). The initial evidence of altered ipRGC function in AMD is shown in a pilot study by , although little is known about the effect of AMD on ipRGC function in various stages of the disease.…”
Section: Intrinsically Photosensitive Retinal Ganglion Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation